Fluoropolyether-containing polysilazane composition and cured film thereof
By using a composite coating composed of polysilicone and nitrogen heterocyclic at room temperature, the problem that existing coatings are difficult to achieve multiple properties at room temperature is solved, and high-performance curing of coatings under single-step processes is achieved, which is suitable for a variety of substrates.
Patent Information
- Application Number
- JP2021193032
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-11-29
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2041-11-29
AI Technical Summary
The existing anti-fouling coatings are difficult to achieve both water, oil, dirt, and hardness at room temperature, and traditional methods require multi-step processes and high-temperature conditions, which limit their application range.
A composite coating consisting of polysilicone-nitrocyclic, containing polysilicone (such as perhydropolysilazane), fluoropolyether with alkoxysilyl hydroxyl, chain aliphatic amino compounds, was used, and cured at room temperature through a single-step coating process.
The coating that cures at room temperature has excellent water, oil, dirt, and hardness properties, and is suitable for a variety of substrates, especially plastic substrates with low heat capacity.
Smart Images

Figure 0007659487000001 
Figure 0007659487000002 
Figure 0007659487000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polysilazane composition and a cured film thereof. [Background technology]
[0002] Objects that are primarily intended for outdoor use, such as the exterior walls and glass windows of buildings and automobile bodies, are exposed to a wide range of pollutants, including dust and organic matter in the air. Although there are no particular problems with the performance of these objects when they become dirty, it is common to apply an anti-fouling coating to the surface as a measure against contamination, as it can lead to a decrease in design and a sense of cleanliness. In particular, the application of an anti-fouling coating is essential for many public buildings, such as public toilets, utility poles, roads, and bridges, as they are visible to many people over a period of several decades.
[0003] Coating agents whose cured film surface exhibits water- and oil-repellency are used for antifouling purposes, and exhibit the function of making it difficult for contaminants to adhere to the surface, and facilitating cleaning even if contaminants do adhere to the surface. Such antifouling coating agents may contain materials containing fluorine atoms (fluorine-based materials). This is because the surface tension of the material is smaller than that of water or oil due to the inclusion of fluorine atoms, and the material exhibits water- and oil-repellency. As a method for antifouling coating using fluorine-based materials, a method of forming a film of fluorine-containing acrylic oligomer using a high-frequency plasma CVD device has been proposed (Patent Document 1). With this method, a coating film that exhibits high strength and high antifouling properties can be formed on the surface of the substrate, but since most outdoor structures undergo antifouling coating treatment after construction, processes that require chambers such as CVD and vapor deposition cannot be adopted.
[0004] In addition, a coating using a low-temperature curing fluoropolymer in which a curable silane compound is modified with a fluoropolyether group (Patent Document 2) has been disclosed. The curable silane compound can also be coated by a wet process. Therefore, compared to dry processes such as CVD and vapor deposition, simple application tools such as sprays and sponges are sufficient, making it possible to coat outdoors.
[0005] On the other hand, when outdoors, collisions with flying stones or the like can cause chipping scratches on the coating or, in some cases, even on the substrate. If only the coating is damaged, it is possible to restore the appearance and function of the coating by recoating, but if the damage is deep enough to reach the substrate, recovery becomes difficult. One way to deal with chipping scratches is to increase the surface hardness of the substrate by using a hard coat. Measures against chipping scratches are particularly important in the coating of objects (e.g., automobiles) that travel outdoors at high speeds. Thus, for example, a resin component for automobiles has been disclosed in which a thermoplastic elastomer layer and a hard coat layer are laminated on a resin substrate (Patent Document 3).
[0006] Coating with a curable silane compound as disclosed in Patent Document 2 forms an ultrathin film similar to a monolayer on the surface of a substrate. Although this film design functions adequately as an antifouling coating, it may not function adequately as a hard coat to protect the substrate from chipping scratches. When the substrate is an inorganic material such as glass or metal, the substrate itself has a high surface hardness, so a coating that focuses only on imparting antifouling properties is sufficient. However, organic materials such as plastics have overwhelmingly inferior surface hardness to inorganic materials such as stone, which are problematic in terms of chipping, and therefore conventional antifouling coating agents are insufficient from the viewpoint of protecting substrates outdoors. Therefore, a hard coat agent using a polysilazane compound and nanosilica has been disclosed as a method of increasing the surface hardness of plastic substrates by focusing on imparting hard coat properties (Patent Document 4). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2015-003510 A [Patent Document 2] JP 2017-082194 A [Patent Document 3] JP 2019-126985 A [Patent Document 4] Patent Publication No. 2021-16995 Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been made to solve the above problems, and an object of the present invention is to provide a polysilazane composition which cures at room temperature of about 25° C. to give a cured film which exhibits excellent water and oil repellency, ease of wiping off dirt, durability and hardness. [Means for solving the problem]
[0009] In order to solve the above problems, the present invention provides a polysilazane composition, comprising: (A) polysilazane, (B) an organic solvent, (C) a fluoropolyether having one or more alkoxysilyl groups in the molecule, and (D) an amine compound having a chain aliphatic amino group, The polysilazane composition comprises:
[0010] Such a polysilazane composition has excellent compatibility between the components and, when cured at room temperature of about 25° C., gives a cured film that exhibits excellent water and oil repellency, dirt wipeability, and hardness.
[0011] In the present invention, the component (A) is preferably perhydropolysilazane.
[0012] Such a polysilazane composition can improve the effects of the present invention.
[0013] In the present invention, the component (D) preferably contains 1 to 3 nitrogen atoms per molecule.
[0014] Such a polysilazane composition can further improve the effects of the present invention.
[0015] In the present invention, the blending amount of the component (D) is preferably 5 to 100 parts by mass per 100 parts by mass of the component (A).
[0016] Such a polysilazane composition can further improve the effects of the present invention.
[0017] In the present invention, the blending amount of the component (C) is preferably 0.1 to 5.0 parts by mass per 100 parts by mass of the total of the components (A) and (B).
[0018] Such a polysilazane composition can further improve the effects of the present invention.
[0019] The present invention also provides a cured film obtained by curing the polysilazane composition.
[0020] Such a cured film exhibits excellent water and oil repellency, ease of wiping off dirt, durability, and hardness, and is therefore useful as a cured film with excellent antifouling properties. Effect of the Invention
[0021] According to the present invention, a polysilazane composition containing a fluoropolyether having one or more alkoxysilyl groups in the molecule and an amine compound having a chain aliphatic amino group can provide a cured film that exhibits excellent water and oil repellency, dirt wiping property, durability and hardness by curing at room temperature of about 25°C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] As mentioned above, anti-fouling coating and hard coat are developed as independent products based on different design concepts. Although it is possible to use them together, there is a problem that the coating process becomes two steps, and if the adhesion between the hard coat layer and the anti-fouling coating layer is not taken into consideration when coating, the functions that each layer is originally capable of exerting cannot be fully obtained.
[0023] Therefore, there is a demand for the development of a coating agent that can provide both antifouling properties and high surface hardness with just one coating step.
[0024] For these reasons, it is believed that a coating agent composed of polysilazane and fluoropolymer as independent components can achieve both anti-fouling properties and high hardness by phase separation into the polysilazane layer and the fluoropolymer layer after application, and there is a demand for the development of technology that contains polysilazane and fluoropolymer as independent components and hardens at room temperature of around 25°C to achieve excellent anti-fouling properties, durability, and hardness.
[0025] In other words, there is a demand for the development of a polysilazane composition that can be applied in just one application and cured at room temperature of about 25° C. to give a cured film that exhibits excellent water and oil repellency, ease of wiping off dirt, and hardness. Therefore, the present inventors have conducted extensive research into the above-mentioned problems and have found that a cured film obtained from a polysilazane composition containing an appropriate combination of a fluoropolyether and an amine compound has excellent water and oil repellency, dirt wiping property, durability and hardness, thereby completing the present invention.
[0026] That is, the present invention is a polysilazane composition, (A) polysilazane, (B) an organic solvent, (C) a fluoropolyether having one or more alkoxysilyl groups in the molecule, and (D) an amine compound having a chain aliphatic amino group, The polysilazane composition comprises:
[0027] The following describes the embodiments of the present invention, but these are presented as examples, and it goes without saying that the present invention is not limited to these and various modifications are possible.
[0028] <Polysilazane Composition> The present invention provides a polysilazane composition comprising (A) polysilazane, (B) an organic solvent, (C) a fluoropolyether having one or more alkoxysilyl groups in the molecule, and (D) an amine compound having a chain aliphatic amino group. The polysilazane composition may contain components other than the components (A) to (D). Each component will be described in detail below.
[0029] <(A) Polysilazane> The polysilazane (A) constituting the polysilazane composition of the present invention forms a glassy cured film by curing. The polysilazane is not particularly limited, but examples thereof include perhydropolysilazane, which is an inorganic polysilazane, or modified polysilazanes such as methylpolysilazane, dimethylpolysilazane, phenylpolysilazane, and vinylpolysilazane, which are organic polysilazanes; crosslinked polysilazanes chemically crosslinked with compounds such as hydrocarbon compounds having reactive groups such as hydroxyl groups, vinyl groups, amino groups, and silyl groups that chemically react with polysilazane to form a crosslinked structure, cyclic saturated hydrocarbon compounds, cyclic unsaturated hydrocarbon compounds, saturated heterocyclic compounds, unsaturated heterocyclic compounds, and silicone compounds; and the like. The polysilazanes can be used by arbitrarily selecting from one type alone, a mixture of polysilazanes selected from two or more types, or a polysilazane copolymer consisting of two or more types of polysilazane structures. The component (A) preferably contains at least one hydrogen atom directly bonded to a silicon atom in one molecule, and perhydropolysilazane is more preferable.
[0030] From the viewpoint of solubility in an organic solvent, which is the component (B) described below, and workability during application, the polysilazane preferably has a weight-average molecular weight in the range of 100 to 100,000,000, preferably 1,000 to 1,000,000, and more preferably 2,000 to 500,000. A weight-average molecular weight of 100 or more is preferable because it has low volatility and there is no risk of the film quality of the coating film deteriorating due to the volatilization of the organic solvent and the volatilization of the polysilazane itself during the curing process, while a weight-average molecular weight of 100,000,000 or less is preferable because it has high solubility in an organic solvent.
[0031] The weight average molecular weight referred to in this specification refers to a value obtained by gel permeation chromatography (GPC) measured under the following conditions using polystyrene as a standard substance. [Measurement conditions] Developing solvent: Tetrahydrofuran (THF) Flow rate: 0.35mL / min Detector: Differential refractive index detector Column: TSKguardcolumn SuperMP(HZ)-M TSKgel SuperMultipore HZ-M (4.6mmI.D.×15cm,4μm×4) (All manufactured by Tosoh Corporation) Column temperature: 40℃ Sample injection volume: 20 μL (THF solution with a concentration of 0.5% by mass)
[0032] <(B) Organic solvent> The polysilazane used in the present invention is diluted with an organic solvent in order to improve workability during application and storage stability. The organic solvent is not particularly limited as long as it dissolves the polysilazane (A), the fluoropolyether (C) having one or more alkoxysilyl groups in the molecule, and the amine compound (D) having a chain aliphatic amino group, which will be described later.For example, saturated aliphatic hydrocarbons such as n-pentane, isopentane, n-hexane, isohexane, n-heptane, isoheptane, n-octane, isooctane, n-nonane, isononane, n-decane, and isodecane; unsaturated aliphatic hydrocarbons such as 1-octene, 1-nonene, 1-decene, 1-dodecene, and β-myrcene; saturated alicyclic hydrocarbons such as cyclopentane, cyclohexane, methylcyclohexane, dimethylcyclohexane, ethylcyclohexane, and decahydronaphthalene; and unsaturated alicyclic hydrocarbons such as cyclohexene. Hydrocarbons, terpene compounds such as p-menthane, d-limonene, l-limonene, and dipentene, aromatic hydrocarbons such as benzene, toluene, xylene, trifluoromethylbenzene, bis(trifluoromethyl)benzene, ethylbenzene, diethylbenzene, trimethylbenzene, triethylbenzene, and tetrahydronaphthalene, acetone, methyl ethyl ketone, diethyl ketone, methyl isobutyl ketone, di-n-butyl ketone, diisobutyl ketone, cyclopentanone, cyclohexanone, and diacetone alcohol. ketone compounds such as n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, isoamyl acetate, ethyl acetoacetate, ethyl caproate, and other ester compounds; alkyl ether compounds such as diethyl ether, di-n-propyl ether, di-n-butyl ether, di-n-pentyl ether, di-n-hexyl ether, and tert-butyl methyl ether; aryl ether compounds such as anisole and diphenyl ether; glycol ether compounds such as bis(2-methoxyethyl)ether, bis(2-ethoxyethyl)ether, and bis(2-butoxyethyl)ether; and fluorous solvents such as tetradecafluorohexane, hexadecafluoropentane, octadecafluorooctane, eicosafluorononane, octafluorocyclopentene, tetradecafluoromethylcyclohexane, octadecafluorodecahydronaphthalene, hexafluorobenzene, 1,3-bis(trifluoromethyl)benzene, octafluorotoluene, and hexafluoroisopropyl methyl ether.
[0033] From the viewpoints of workability during application and storage stability of polysilazane, the dilution ratio is preferably within the range of 100 to 100,000 parts by mass, and more preferably 400 to 10,000 parts by mass, of the organic solvent (B) per 100 parts by mass of the polysilazane (A).
[0034] The (B) organic solvents may be used alone or in combination of two or more kinds.
[0035] The water content in the polysilazane composition of the present invention is preferably 500 ppm or less, more preferably 300 ppm or less. If the water content is 500 ppm or less, polysilazane and the contained water do not react with each other, so there is no risk of heat generation, hydrogen gas or ammonia gas generation, and there is no risk of thickening or gelation. Therefore, it is preferable that the water content in the (B) organic solvent is controlled so that the water content in the polysilazane composition of the present invention is within the above range.
[0036] <(C) Alkoxysilyl Group-Containing Fluoropolyether> (C) fluoropolyether having one or more alkoxysilyl groups in the molecule (alkoxysilyl group-containing fluoropolyether) is contained in the polysilazane composition of the present invention, and serves to impart water and oil repellency and antifouling properties to the cured film obtained from the polysilazane composition of the present invention. Specifically, in the curing process of the polysilazane composition of the present invention, the alkoxysilyl group is condensed, and the alkoxysilyl group-containing fluoropolyether (C) is bonded to the polysilazane (A), thereby obtaining a cured film that exerts the effects of the present invention.
[0037] (C) The alkoxysilyl group-containing fluoropolyether may have a divalent linear fluoropolyether group represented by the following formula (c-1) in the molecule. -(CF2O) p (CF2CF2O) q (CF2CF2CF2O) r (CF2CF2CF2CF2O) s - (c-1)
[0038] The values of p, q, r, and s above are 19 It is a value obtained from the integral ratio of F NMR, where p is an integer of 1 or more, preferably 1 to 80, and more preferably 3 to 30, q is an integer of 1 or more, preferably 1 to 80, and more preferably 3 to 30, r is an integer of 0 or more, preferably 0 to 20, and more preferably 0 to 5, and s is an integer of 0 or more, preferably 0 to 20, and more preferably 0 to 5, and each repeating unit may be bonded randomly. Since the above-mentioned water and oil repellency and antifouling properties are due to the presence of fluorine atoms, compatibility with the polysilazane composition is good when p and q are 1 or more and p, q, r, and s are within the above-mentioned ranges.
[0039] The alkoxysilyl group in the above fluoropolyether can be represented by the following formula (c-2). -Si(OR c1 ) m R c2 n (c-2) In the formula, m is an integer satisfying 1≦m≦3, n is an integer satisfying 0≦n≦2, and m+n=3, and it is preferable that m is 3 and n is 0.
[0040] OR c1 represents an alkoxy group bonded directly to a silicon atom, and OR c1 The oxygen atom of the above is directly bonded to a silicon atom to form an alkoxysilyl group.
[0041] R c1 Examples of the alkyl group include hydrocarbon groups such as a methyl group, an ethyl group, a propyl group, a butyl group, a vinyl group, a cyclohexyl group, and a phenyl group; ether bond-containing hydrocarbon groups such as a methoxymethyl group, a benzyloxymethyl group, and a methoxyethoxymethyl group; and thioether bond-containing hydrocarbon groups such as a methylthiomethyl group. Of these, a methyl group is preferred.
[0042] R c2is a group other than an alkoxy group, and examples thereof include hydrocarbon groups such as a methyl group, an ethyl group, a propyl group, a butyl group, a vinyl group, a cyclohexyl group, and a phenyl group; ether bond-containing hydrocarbon groups such as a methoxymethyl group, a benzyloxymethyl group, and a methoxyethoxymethyl group; and thioether bond-containing hydrocarbon groups such as a methylthiomethyl group. Of these, a methyl group is preferred.
[0043] The divalent linear fluoropolyether group represented by (c-1) and the alkoxysilyl group represented by (c-2) are linked via a linking group. The linking group improves the solubility of the alkoxysilyl group-containing fluoropolyether (C) in the organic solvent (B), thereby enhancing the compatibility with the polysilazane composition of the present invention.
[0044] As long as the divalent linear fluoropolyether group represented by (c-1) above and the alkoxysilyl group represented by (c-2) above are covalently linked via a molecular chain consisting of a divalent or higher linking group, the structure of the molecular chain of the divalent or higher linking group is not particularly limited.
[0045] By using a trivalent or higher linking group to increase the number of alkoxysilyl groups contained, the effects of the present invention can be improved.
[0046] In order to avoid a decrease in the compatibility of the fluoropolyether with the polysilazane composition of the present invention due to the increase in molecular weight of the fluoropolyether resulting from intramolecular condensation of the alkoxysilyl group, the valence of the linking group is preferably 2 to 10, more preferably 2 to 5.
[0047] The above-mentioned linking group may be one which is mediated by one or more types of structures selected from an ether bond, an amide bond, an ester bond, and a siloxane bond.
[0048] The linking group links (c-1) and (c-2) via it, and may contain a branched or cyclic structure, and the number of atoms derived from the linking group is preferably 2 to 50, and more preferably 4 to 30. When the number of atoms is 50 or less, the amount of fluorine atoms per weight contained in the additive (C) component does not decrease, and therefore the antifouling performance does not decrease.
[0049] Examples of the linking group include -CF2CH2O(CH2)3-.
[0050] The (C) alkoxysilyl group-containing fluoropolyethers may be used alone or in combination of two or more kinds.
[0051] The blending amount of component (C) (alkoxysilyl group-containing fluoropolyether) is preferably 0.1 to 5.0 parts by mass, more preferably 0.1 to 1.0 part by mass, and even more preferably 0.2 to 0.6 parts by mass, per 100 parts by mass of the combined total of component (A) (polysilazane) and component (B) (organic solvent).
[0052] Examples of (C) alkoxysilyl group-containing fluoropolyethers include KY-1281 (manufactured by Shin-Etsu Chemical Co., Ltd.) (a solution of alkoxysilyl group-containing fluoropolyether dissolved in MEK, with an active ingredient concentration of 20% by mass) and those represented by the following formula CB. [ka]
[0053] <(D) Amine compound having a chain aliphatic amino group> The component (D) (amine compound having a chain aliphatic amino group) has the effect of improving the fixing efficiency of the component (C) in the cured film obtained from the polysilazane composition of the present invention, thereby imparting dirt wiping properties, and further has the effect of improving the abrasion resistance and hardness of the cured film by increasing the curing reaction rate of the polysilazane of the component (A).
[0054] The amine compound of component (D) is not particularly limited as long as it has an amino group substituted with a chain-like aliphatic hydrocarbon group (chain-like aliphatic amino group), and the aliphatic hydrocarbon group may have a trialkoxysilyl group, may be linear or branched, nitrogen atoms may be linked to each other via an aliphatic hydrocarbon group, and may be substituted with a heteroatom other than a nitrogen atom, such as an oxygen atom. When the aliphatic hydrocarbon group is monovalent, it is preferably a trialkoxysilyl-modified alkyl group or a linear alkyl group, more preferably a trialkoxysilyl-modified alkyl group having 2 to 6 carbon atoms or a linear alkyl group having 4 to 12 carbon atoms, and when it is divalent, it is preferably a linear alkylene group, more preferably a linear alkylene group having 3 to 8 carbon atoms. When the amine compound of component (D) is cyclic, it is inferior in dirt wiping property, durability, and hardness. The effect of component (D) is due to the basicity of component (D). When component (D) is cyclic, the basicity may be very high compared to chain-like aliphatic amines. In this case, the curing reaction rate of component (A) is accelerated too much, preventing phase separation between the polysilazane layer and the fluoropolymer layer, resulting in the fluoropolymer remaining in the polysilazane layer, which is thought to result in poor film properties as described above.
[0055] The structure of the amine compound having a chain aliphatic amino group used in the present invention is not particularly limited as long as it can serve as a catalyst for a curing reaction when left to stand at room temperature or irradiated with UV light, and examples of such amine compounds include methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, n-propylamine, isopropylamine, di-n-propylamine, diisopropylamine, tri-n-propylamine, triisopropylamine, n-butylamine, sec-butylamine, isobutylamine, tert-butylamine, di-n-butylamine, di- sec-butylamine, diisobutylamine, di-tert-butylamine, tri-n-butylamine, tri-sec-butylamine, triisobutylamine, tri-tert-butylamine, n-pentylamine, 2-pentylamine, 3-pentylamine, isopentylamine, neopentylamine, di-n-pentylamine, diisopentylamine, dineopentylamine, tri-n-pentylamine, triisopentylamine, trineopentylamine, n-hexylamine, di-n-hexylamine, tri-n-hexylamine, n-o Octylamine, di-n-octylamine, tri-n-octylamine, 1,2-diaminoethane, N,N'-dimethyl-1,2-diaminoethane, N,N,N',N'-1,2-tetramethyldiaminoethane, 1,3-diaminopropane, N,N'-dimethyl-1,3-diaminopropane, N,N,N',N'-1,3-tetramethyldiaminopropane, 1,4-diaminobutane, N,N'-dimethyl-1,4-diaminobutane, N,N,N',N'-1,4-tetramethyldiaminobutane, 1,5-diaminopentane, N,N'-dimethyl-1, 5-Diaminopentane, N,N,N',N'-1,5-tetramethyldiaminopentane, 1,6-diaminohexane, N,N'-dimethyl-1,6-diaminohexane, N,N,N',N'-tetramethyl-1,6-diaminohexane, N,N-bis(3-aminopropyl)amine, N,N-bis[3-(methylamino)propyl]amine, N,N-bis[3-(dimethylamino)propyl]amine, N-methyl-N,N-bis(3-aminopropyl)amine, N-methyl-N,N-bis[3-(methylamino)propyl]amine, N-methyl-N,aliphatic amines such as N-bis[3-(dimethylamino)propyl]amine; alkoxysilyl group-containing aliphatic amines such as 3-aminopropyltriethoxysilane and N-2-(aminoethyl)-3-aminopropyltrimethoxysilane; aliphatic amino alcohols such as ethanolamine, N-methylethanolamine, N,N-dimethylethanolamine, N-ethylethanolamine, N,N-diethylethanolamine, N-methyl-N-ethylethanolamine, N-benzylethanolamine, N,N-dibenzylethanolamine, and diethylene glycolamine; 2-methoxyethylamine, 2-ethoxyethylamine, 2-n-propoxyethylamine, 2-isopropoxyethylamine, 2-n-butoxyethylamine, 2-methoxypropylamine, 2-ethoxypropylamine, 2-n-propoxypropylamine, 2-isopropoxypropylamine, 2-n-butoxypropylamine; , 3-methoxypropylamine, 3-ethoxypropylamine, 3-n-propoxypropylamine, 3-isopropoxypropylamine, 3-n-butoxypropylamine, 2-methoxybutylamine, 2-ethoxybutylamine, 2-n-propoxybutylamine, 2-isopropoxybutylamine, 2-n-butoxybutylamine, 3-methoxybutylamine, 3-ethoxybutylamine, 3-n-propoxybutylamine, 3-isopropoxybutylamine, 3-n-butoxybutylamine, 4-methoxybutylamine, 4-ethoxybutylamine, 4-n-propoxybutylamine, 4-isopropoxybutylamine, 4-n-butoxybutylamine, bis(2-aminoethyl)ether, bis(3-aminopropyl)ether, bis(4-aminobutyl)ether, 1,4-butanediol bis(2-aminoethyl)ether, 1,4-butanediol bis(3-aminopropyl)ether, 1,Examples of the amino ethers include aliphatic amino ethers such as 4-butanediol bis(4-aminobutyl) ether, bis[2-(2-aminoethoxy)ethyl] ether, bis[2-(3-aminopropoxy)ethyl] ether, bis[2-(4-aminobutoxy)ethyl] ether, triethylene glycol bis(2-aminoethyl) ether, triethylene glycol bis(3-aminopropyl) ether, and triethylene glycol bis(4-aminobutyl) ether.
[0056] (D) The amine compounds having a chain aliphatic amino group may be used alone or in combination of two or more kinds.
[0057] The number of nitrogen atoms contained in one molecule of the (D) amine compound having a chain aliphatic amino group is preferably 1 to 3. When the number of nitrogen atoms contained in one molecule is 1 to 3, the lipophilicity of the (D) component is sufficient, and the compatibility with the polysilazane composition is good.
[0058] The blending amount of (D) the amine compound having a chain aliphatic amino group is preferably 5 to 100 parts by mass, and more preferably 10 to 50 parts by mass, per 100 parts by mass of (A) the polysilazane. When the blending amount is 5 parts by mass or more, the effect of the (D) component is sufficiently obtained, and when it is 100 parts by mass or less, there is no risk of the hardness of the cured film being significantly reduced.
[0059] <Other additives> The polysilazane composition of the present invention may contain additives other than those mentioned above depending on the purpose. For example, inorganic fillers such as silica, alumina, and titania may be added as additives to improve the properties (coating strength, heat resistance) of the cured film. For example, ultraviolet absorbers such as benzophenone compounds and / or light stabilizers such as hindered amine compounds may be added as additives to improve weather resistance.
[0060] <Cured film> In the present invention, the polysilazane composition can be cured to form a cured film. Such a cured film exhibits excellent water and oil repellency, dirt wiping property, and durability, and is therefore useful as a cured film with excellent antifouling properties.
[0061] <Method of producing polysilazane composition> The polysilazane composition of the present invention may be produced by any method without limitation. For example, a polysilazane composition in which each component is suitably dissolved can be obtained by adding components (C) and (D) to a solution obtained by mixing components (A) and (B), and then, for example, shaking and stirring the mixture.
[0062] <Method of forming a cured film> The method for forming a cured film using the polysilazane composition of the present invention is not particularly limited, and examples thereof include a method including a coating step of coating the polysilazane composition on a substrate, a solvent volatilization step of volatilizing and removing the organic solvent from the coating film coated on the substrate, and a curing step of curing the polysilazane composition components other than the organic solvent.
[0063] (coating process) Examples of methods for applying the polysilazane composition of the present invention to a substrate include roll coating methods using a direct gravure coater, a chamber doctor coater, an offset gravure coater, a reverse kiss coater, a reverse roll coater, a slot die, a lip coater, an air doctor coater, a single roll kiss coater, a positive rotation roll coater, a blade coater, an impregnation coater, an MB coater, an MB reverse coater, a knife coater, a bar coater, etc., spin coating methods, dispensing methods, dipping methods, spraying methods, transfer methods, slit coating methods, etc.
[0064] The thickness of the coating film varies depending on the purpose of the cured film, but the cured film thickness is preferably 10 to 100,000 nm, and more preferably 100 to 10,000 nm.
[0065] Before applying the polysilazane composition, the substrate may be subjected to a surface modification treatment. The surface modification treatment is mainly performed for the purpose of improving the adhesion between the substrate and the polysilazane, and is realized by decomposing and removing organic matter attached to the substrate surface, or by forming chemical reaction points on the substrate surface. Examples of the surface modification treatment method include argon plasma treatment, oxygen plasma treatment, ozone treatment, UV irradiation treatment, and xenon excimer light irradiation treatment, and are used depending on the type of substrate.
[0066] <Base material> The substrate may be made of any suitable material, such as glass, resin (which may be a natural or synthetic resin, for example a common plastic material, and may be in the form of a plate, film, or other form), metal (which may be a simple metal such as aluminum, copper, iron, or a composite such as an alloy), ceramics, semiconductors (silicon, germanium, etc.), fibers (woven fabrics, nonwoven fabrics, etc.), fur, leather, wood, ceramics, stone, etc., building materials, etc.
[0067] (Solvent evaporation process) Following the coating step, the process proceeds to a solvent evaporation step in which the organic solvent is evaporated from the coating film formed on the substrate. The solvent evaporation step may be performed at a temperature at which the substrate does not deteriorate, and is preferably performed at, for example, 20 to 300°C. Within this range, the organic solvent evaporates quickly and the process can proceed to the curing step. If the temperature of the solvent evaporation step is 300°C or less, there is no risk of the evaporated solvent igniting, and this is preferable.
[0068] For the above reasons, the boiling point of the (B) organic solvent used in the present invention under atmospheric pressure (1013 hPa) is preferably 25 to 300° C., and more preferably 25 to 150° C. If it is within this range, the organic solvent will not remain in the cured film, and handling properties will be good.
[0069] (hardening process) After the solvent evaporation process, the process proceeds to hardening the polysilazane containing fluoropolyether (component (C)) and amine compound (component (D)). There are no particular restrictions on the hardening process of the fluoropolyether (fluorine polymer, etc.) and the polysilazane containing amine compound as long as the hardening reaction proceeds, but it is necessary to select an appropriate method that does not alter the base material. Examples of hardening process methods include leaving the material at rest under constant temperature and humidity, atmospheric pressure plasma treatment, low-temperature plasma treatment, UV treatment, and excimer light treatment. EXAMPLES
[0070] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. The weight average molecular weight refers to the value obtained by gel permeation chromatography (GPC) using polystyrene as a standard substance as described above.
[0071] (A) Polysilazane (Synthesis example) Synthesis of polysilazane (A) Dehydrated pyridine (4,500 g) was cooled to -10°C under a nitrogen atmosphere, and dichlorosilane (64 L) was blown in, followed by stirring at -10°C for 1 hour. Ammonia (216 L) was blown in, and the mixture was stirred for 12 hours while returning to 25°C. The resulting solid was filtered off, and di-n-dibutyl ether (1,000 g) was added to the filtrate. The pyridine in the liquid was distilled off under reduced pressure while azeotroping with di-n-butyl ether, and when the distillate reached 4,500 g, di-n-butyl ether (1,000 g) was further added. Subsequently, pyridine was distilled off under reduced pressure while azeotroping with di-n-butyl ether to obtain a di-n-butyl ether solution of perhydropolysilazane. The weight-average molecular weight of this perhydropolysilazane was 6,100. Thereafter, di-n-butyl ether was added so that the amount of polysilazane was 2.5 parts by mass when the entire solution was 100 parts by mass. In the following examples and comparative examples, this solution was used assuming that it contained 2.5 parts by mass of perhydropolysilazane as component (A) and 97.5 parts by mass of di-n-butyl ether as component (B-1). When 1,3-bis(trifluoromethyl)benzene was contained as component (B-2), it was used assuming that it contained 2.5 parts by mass of component (A), 47.5 parts by mass of component (B-1), and 50 parts by mass of component (B-2).
[0072] (B) Organic solvent (B-1): Di-n-butyl ether (Kanto Chemical) (B-2): 1,3-bis(trifluoromethyl)benzene (Tokyo Chemical Industry Co., Ltd.)
[0073] (C) Fluoropolyether having one or more alkoxysilyl groups in the molecule Treatment liquid (C-1): KY-1281 (manufactured by Shin-Etsu Chemical Co., Ltd.) (a solution containing alkoxysilyl-containing fluoropolyether dissolved in MEK with an active ingredient concentration of 20% by mass) Treatment solution (C-2): A solution with an active ingredient concentration of 20% by mass, in which the CB synthesized below is dissolved in the component (B-2).
[0074] Synthesis of precursor (CA) Fomblin D2 (Solvay) (50 g), 30% by mass sodium hydroxide aqueous solution (6 g), and tetrabutylammonium hydrogen sulfate (0.4 g) were placed in a 100 mL three-neck flask. Allyl bromide (12 g) was added while stirring, and the mixture was heated at an internal temperature of 50°C for 24 hours. 2.4 M hydrochloric acid (12 g), 1,3-bis(trifluoromethyl)benzene (40 g), and pure water (40 g) were added, and after shaking, the organic layer and the aqueous layer were separated. The organic layer was washed four times with pure water (40 g). Activated carbon (Shirasagi P) (Osaka Gas Chemical) (0.4 g) and Kyoward 2200 (Kyowa Chemical Industry) (0.4 g) were added to the organic layer, and the mixture was stirred at room temperature for 1 hour. The mixture was filtered and the solvent was distilled off under reduced pressure to obtain the precursor (CA) as a colorless transparent liquid with a yield of 85%.
[0075] Synthesis of the active ingredient (CB) of the treatment liquid (C-2) The CA (10 g), 1,3-bis(trifluoromethyl)benzene (20 g), and platinum catalyst (CAT-PL-50T, manufactured by Shin-Etsu Chemical Co., Ltd.) (0.015 g) were added to a 100 mL three-neck flask, and the mixture was heated to an internal temperature of 60°C, after which trimethoxysilane (03-MS, manufactured by Shin-Etsu Chemical Co., Ltd.) (1.5 g) was added dropwise. After heating and stirring at an internal temperature of 60°C for 5 hours, activated carbon (0.5 g) was added and the mixture was stirred for 1 hour while returning to room temperature. The mixture was filtered and the solvent was distilled off under reduced pressure to obtain the active ingredient (CB) as a colorless, transparent liquid with a yield of 97%. [ka]
[0076] Preparation of treatment solution (C-2) The CB synthesized above was dissolved in component (B-2) to prepare a solution with an active ingredient concentration of 20 mass %.
[0077] Preparation of treatment solution (C-3); for comparison Treatment liquid (C-3): A fluoropolyether containing a polyether group not having an alkoxysilyl group (product name: Fluorolink PEG45 (manufactured by Solvay)) was dissolved in component (B-2) to prepare a solution with an active ingredient concentration of 20% by mass.
[0078] (D) Amine compounds having a chain aliphatic amino group (D-1): 3-aminopropyltriethoxysilane (KBE-903 manufactured by Shin-Etsu Chemical Co., Ltd.) (D-2): Hexylamine (Tokyo Chemical Industry Co., Ltd.) (D-3): N,N,N',N'-tetramethyl-1,6-diaminohexane (Tokyo Chemical Industry Co., Ltd.) (D-4): 3,3'-iminobis(N,N-dimethylpropylamine) (Tokyo Chemical Industry Co., Ltd.)
[0079] Amine compounds; for comparison (D-5): 1,8-diazabicyclo[5.4.0]-7-undecene (Tokyo Chemical Industry Co., Ltd.)
[0080] [Examples 1 to 13, Comparative Examples 1 to 3] (1) Evaluation of water contact angle and hexadecane contact angle (Preparation of solutions) The components (A) and (B-1) prepared in the above Synthesis Examples were mixed in the ratios shown in Table 1 to prepare a solution, to which the components (C) and (D) prepared above, and optionally the component (B-2) were added, and the container was shaken and stirred for 10 seconds to prepare a polysilazane composition.
[0081] (coating process) The solution prepared above was spin-coated onto soda glass (rotation speed: 500 rpm, rotation time: 30 seconds).
[0082] (Solvent evaporation process and hardening process) The polysilazane composition thus applied was allowed to stand for 24 hours in an environment at a temperature of 24° C. and a relative humidity of 40%. The contact angles of water or hexadecane with the cured films prepared above were measured using a contact angle meter Dropmaster DMo-701 (manufactured by Kyowa Interface Science). The measured contact angle values are shown in Table 1.
[0083] (2) Evaluation of oil-based pen wiping properties A curved line 5 cm long was drawn on the cured film prepared in the evaluation of (1) above using an oil-based pen (Pentel Pen N50, manufactured by Pentel). The drawn curve was wiped off with Kaydry (manufactured by Nippon Paper Crecia). In Table 1, those in which all the ink from the oil-based pen could be wiped off within three wipes were given an ◯, and those that required four or more wipes or could not be wiped off were given an ×.
[0084] (3) Evaluation of wear resistance The surface of the cured film prepared in the evaluation in (1) above was abraded using Tribogear (manufactured by Shinto Scientific Co., Ltd.) under the following conditions. Thereafter, the water contact angle was measured in the same manner as in the evaluation in (1) above. Those with a water contact angle of 100° or more were marked with an ◯, and those with a water contact angle of less than 100° were marked with an ×, as shown in Table 1. [Wear conditions] Friction material: Bencot Super CN (made by Asahi Kasei) Contact area: 3.0cm x 2.8cm Load capacity: 1kg Rubbing distance (one way): 30mm Scraping speed: 5,400 mm / min Number of trips: 1,000
[0085] (4) Evaluation of pencil hardness The pencil hardness of the cured film produced in the evaluation in (1) above was measured with a pencil hardness tester (manufactured by Paperless Manufacturing Co., Ltd.) and a pencil (Mitsubishi Pencil Co., Ltd. Hi-Uni 6B to 6H) under a load of 750 g. The results are shown in Table 1.
[0086] In Table 1, the units of each component are parts by mass.
[0087] [Table 1]
[0088] Since Comparative Example 1 does not contain the (D) component, the (C) component is insufficiently fixed to the surface, and therefore the oil-based pen wiping property and abrasion resistance are inferior. Furthermore, since Comparative Example 1 does not contain the (D) component, the (A) component is insufficiently cured, and therefore the hardness is significantly inferior to Examples 1 to 13. Since the (C) component contained in Comparative Example 2 and the (D) component contained in Comparative Example 3 do not match the structure of the present invention, they are inferior to Examples 1 to 13 in at least three evaluation items.
[0089] [Industrial Applicability] The polysilazane composition of the present invention is useful as an antifouling coating composition, and can form a cured film having excellent water and oil repellency, antifouling properties, durability and hardness at room temperature. Therefore, it is useful for forming the above-mentioned cured film on a substrate having low heat resistance or in an outdoor coating environment where heating is difficult.
[0090] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention.
Claims
1. 1. A polysilazane composition comprising: (A) polysilazane, (B) an organic solvent, (C) a fluoropolyether having one or more alkoxysilyl groups in the molecule, and (D) an amine compound having a chain aliphatic amino group, wherein the (B) organic solvent is an organic solvent that dissolves the (A) component, the (C) component, and the (D) component.
2. 2. The polysilazane composition according to claim 1, wherein the component (A) is a perhydropolysilazane.
3. 3. The polysilazane composition according to claim 1, wherein the number of nitrogen atoms contained in one molecule of the component (D) is 1 to 3.
4. 4. The polysilazane composition according to claim 1, wherein the blending amount of the component (D) is 5 to 100 parts by mass per 100 parts by mass of the component (A).
5. The polysilazane composition according to any one of claims 1 to 4, wherein the blending amount of the component (C) is 0.1 to 5.0 parts by mass per 100 parts by mass of the total of the components (A) and (B).
6. A cured film obtained by curing the polysilazane composition according to any one of claims 1 to 5.
Citation Information
Patent Citations
Method for producing modified silica film, coating liquid, and modified silica film
JP2014213317A
Laminate
JP2015003510A
Perfluoro(POLY)ether group-containing silane compound
JP2017082194A
Perfluoro (POLY) ether group-containing silane compound
JP2019070100A
Resin member for vehicle
JP2019126985A